Biomimetic enzyme barrier for preventing intestine-derived LPS induced diseases. Issue 15 (3rd March 2020) - Zhao, Cheng; Kao, Xiaoming; Wang, Zhiwei; Liu, Qinjie; Wu, Jie; Hu, Qiongyuan; Wu, Xiuwen; Ren, Jianan
Abstract : Biomimetic enzyme barrier (BEB) encapsulated microcapsules could prevent intestine-derived LPS induced diseases. Abstract : Biomimetic enzyme barrier (BEB) encapsulated microcapsules with alginate shells were in situ fabricated with a microfluidic electrospray approach for preventing intestine-derived LPS induced diseases. As the alginate shells could protect the contents in gastric juice and release them in the intestine, the inner BEB could form a consecutive immune barrier on the surface of the intestine during the release. Through combining BEB with alkaline phosphatase, the immune barrier could degrade and prevent the permeation of lipopolysaccharide, which enhanced the intestinal barrier function. Thus, the BEB microcapsules were imparted with outstanding ability in preventing intestine-derived LPS induced diseases. Based on an in vivo study, we demonstrated that this BEB microcapsule could effectively protect organ function, restore intestinal barrier integrity, prevent the permeation of LPS and alleviate inflammation. Therefore, the generated microcapsules have potential for clinical applications.